Application of signal analysis techniques for condition monitoring of a wire bonding machine - Ahmad, Puteri Aidawati (ieee, 2000)

(untitled)
This paper investigates the technique to monitor the condition of a wire bonding machine that used in the integrated manufacturing (IC) industry. The machine forms the connection between the bonding pad on the die to the contacts of the leadframe. To ensure consistency in the process, defects in the bondhead subassembly can be monitored from the damping signature. For this purpose, the analysis techniques chosen are the correlation function and power spectrum estimation. Thus, the main objective of this paper is to find the signal analysis technique that can uniquely represent the good from the defective machine signatures